Evidence for the spread of SARS-CoV-2 and olfactory cell lineage impairment in close-contact infection Syrian hamster models - Ueha, Rumi; Ito, Toshihiro; Ueha, Satoshi; Furukawa, Ryutaro; Kitabatake, Masahiro; Ouji-Sageshima, Noriko; Uranaka, Tsukasa; Tanaka, Hirotaka; Nishijima, Hironobu; Kondo, Kenji; Yamasoba, Tatsuya (Frontiers in Cellular and Infection Microbiology, 2022)
Objectives Close contact with patients with COVID-19 is speculated to be the most common cause of viral transmission, but the pathogenesis of COVID-19 by close contact remains to be elucidated. In addition, despite olfactory impairment being a unique complication of COVID-19, the impact of SARS-CoV-2 on the olfactory cell lineage has not been fully validated. This study aimed to elucidate close-contact viral transmission to the nose and lungs and to investigate the temporal damage in the olfactory receptor neuron (ORN) lineage caused by SARS-CoV-2. Methods Syrian hamsters were orally administered SARS-CoV-2 nonvariant nCoV-19/JPN/TY/WK521/2020 as direct-infection models. On day 3 after inoculation, infected and uninfected hamsters were housed in the same cage for 30 minutes. These uninfected hamsters were subsequently assigned to a close-contact group. First, viral presence in the nose and lungs was verified in the infection and close-contact groups at several time points. Next, the impacts on the olfactory epithelium, including olfactory progenitors, immature ORNs, and mature ORNs were examined histologically. Then, the viral transmission status and chronological changes in tissue damage were compared between the direct-infection and close-contact groups. Results In the close-contact group, viral presence could not be detected in both the nose and lungs on day 3, and the virus was identified in both tissues on day 7. In the direct-infection group, the viral load was highest in the nose and lungs on day 3, decreased on day 7, and was no longer detectable on day 14. Histologically, in the direct-infection group, mature ORNs were most depleted on day 3 (p <0.001) and showed a recovery trend on day 14, with similar trends for olfactory progenitors and immature ORNs. In the close-contact group, there was no obvious tissue damage on day 3, but on day 7, the number of all ORN lineage cells significantly decreased (p <0.001). Conclusion SARS-CoV-2 was transmitted even after brief contact and subsequent olfactory epithelium and lung damage occurred more than 3 days after the trigger of infection. The present study also indicated that SARS-CoV-2 damages all ORN lineage cells, but this damage can begin to recover approximately 14 days post infection.